2011
DOI: 10.2319/091710-541.1
|View full text |Cite
|
Sign up to set email alerts
|

Informational value and bias of videos related to orthodontics screened on a video-sharing Web site

Abstract: Objective: To assess the informational value, intention, source, and bias of videos related to orthodontics screened by the video-sharing Internet platform YouTube. Methods: YouTube (www.youtube.com) was scanned in July 2010 for orthodontics-related videos using an adequately defined search term. Each of the first 30 search results of the scan was categorized with the system-generated sorts ''by relevance '' and ''most viewed'' (total: 60). These were rated independently by three assessors, who completed a que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
90
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(99 citation statements)
references
References 21 publications
(23 reference statements)
7
90
0
2
Order By: Relevance
“…In another Twitter analysis, 3 researchers assessed the ''tweets'' from patients receiving Invisalign or fixed orthodontic treatments and reported a significant number of positive posts for orthodontic treatment, but no significant differences between these two treatment methods. Knösel and Jung 23 conducted a study to measure the level of knowledge in orthodontic posts in YouTubee and concluded that while YouTubee is a platform where patient experiences are shared, the relevant videos were insufficient in terms of content. Since feedback from these shares/posts constitutes one of the external factors that determines the attitudes of patients toward orthodontic treatment, it can be anticipated that studies evaluating the level of content on social media will increase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another Twitter analysis, 3 researchers assessed the ''tweets'' from patients receiving Invisalign or fixed orthodontic treatments and reported a significant number of positive posts for orthodontic treatment, but no significant differences between these two treatment methods. Knösel and Jung 23 conducted a study to measure the level of knowledge in orthodontic posts in YouTubee and concluded that while YouTubee is a platform where patient experiences are shared, the relevant videos were insufficient in terms of content. Since feedback from these shares/posts constitutes one of the external factors that determines the attitudes of patients toward orthodontic treatment, it can be anticipated that studies evaluating the level of content on social media will increase.…”
Section: Discussionmentioning
confidence: 99%
“…The level of content of videos in the field of orthodontics on YouTubee and posts on other social media tools have been assessed in previous studies. 3,8,[23][24][25] Al-Silwadi et al 8 investigated the importance of social media in increasing the knowledge level of patients receiving fixed orthodontic treatment and found that social media tools that convey audiovisual information, such as YouTubee, increased the knowledge level of orthodontic patients. In addition, Henzell et al 24 concluded in their study of Twitter posts about orthodontics that patients stated their positive and negative feelings about their braces.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] There has been little research on the effectiveness of online information in improving patient knowledge; however, it has been shown that orthodontic patients use the Internet for treatment-related information. 15 …”
mentioning
confidence: 99%
“…As social media platforms allow videos to quickly reach a broad audience (Backinger et al, 2011;Carson, 2011;Keelan et al, 2007;Knosel & Jung, 2011), future research should evaluate social media's role on conveying agricultural and food topics on short videos. In addition, given that research on how types of devices used to view advertising videos made a difference in viewers' preference and purchase intent in the area of automotive and quick casual restaurants (The Interactive Advertising Bureau, 2016), it is valuable to record data about the device respondents used to view videos and assess if viewers' attitudes differ by device type.…”
Section: Recommendations For Researchmentioning
confidence: 99%
“…If used thoughtfully, video interventions also provide consistent delivery of educational messages in a variety of formats: videotapes, downloaded media files, or streaming videos on Internet websites (Gagliano, 1988). Videos shared on social media can quickly reach a broad audience making them an effective means of message communication (Backinger et al, 2011;Carson, 2011;Keelan, Pavri-Garcia, Tomlinson, & Wilson, 2007;Knosel & Jung, 2011). Special interest groups have successfully utilized online video campaigns to communicate about food, for example, Only Organic's New Macdonald song campaign and Chipotle's Cultivate Festival directly targeted their consumers (Schroeder, 2015).…”
mentioning
confidence: 99%